Risk and protective factors for postpartum depression among Polish women - a prospective study - Sebastian Klein; Magdalena Błażek; Dariusz Świetlik (Taylor & Francis Group, 2024)
AbstractThis prospective study conducted at a single center in 2022 aims to identify risk and protective factors for postpartum depression (PPD) in Polish women and to assess the impact of pregnancy, delivery, the postpartum period, and psychosocial factors on PPD. After delivery and 4 weeks later, 311 women filled out two questionnaires of our design related to risk factors for PPD. Immune Power Personality Questionnaire, Walsh Family Resilience Questionnaire, and Edinburg Postnatal Depression Scale were also applied. The predictors of PPD identified at two time points included: use of antidepressants, previous depressive episodes, family history of depression, risk of preterm delivery, anxiety about child's health, and breastfeeding and sleep problems. Risk factors for PPD found only after delivery were: suicidal ideation before pregnancy, stressful life events, premature rupture of the membranes, and cesarean section. Inhalation analgesia during labor reduced the PPD frequency. At 4 weeks' postpartum, regular physical activity was also predictive of PPD, while breastfeeding, financial satisfaction, and sufficient sleep duration were protective factors. PPD after delivery was negatively correlated with capacity to confide, hardiness, assertiveness, self-complexity, and communication. PPD at 4 weeks postpartum decreased belief systems, organization patterns, and communication. Two proposed self-designed questionnaires can be useful for effectively screening PPD in the Polish population.